Nuda podróżowania, nuda czekania. "Gerry" Gusa Van Santa a teatr Samuela Becketta - Popielecki, Jakub (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2009)
Boredom of travelling, boredom of waiting. Gus Van Sant’s “Gerry” and the theatre of Samuel Beckett Jakub Popielecki draws on Roger Ebert’s anecdote and discusses similarities between Gus Van Sant’s Gerry and the theatre of Samuel Beckett. The movie and Beckett’s plays (such as Waiting for Godot) share many components: a sexually ambiguous pair of main characters, Buster Keaton’s physical comedy as a source of inspiration and use of wordplay in the title. Is Van Sant’s film a rethinking of “Beat Generation”-inspired road movie mythology? Are the characters played by Matt Damon and Casey Affleck nomads (as described by Gilles Deleuze)? What connects Van Sant’s and Beckett’s works with the phenomenon of boredom? Popielecki sees the minimalist style of these artists as a sign of a new attitude towards the problem of aesthetic experience.